Fitrah-Based Islamic Education in Instilling Religious Values in Children in the Digital Era at the Institution of “Batas” Depok - Camilia, Diana Faricha; Al Ghifary, Ubaidillah; Rena, Syahidah (ARZUSIN, 2025)
In the digital era, education has a tough challenge in internalizing religious values to children. This study aims to comprehensively analyze Fitrah-based Islamic education in cultivating children's religious values at BATAS (Belajar Al Qur'an sampai Tuntas / Learning the Qur'an Until Complete) institution. Researchers used qualitative research with the type of case study—data collection through observation, interviews, and documentation. The data were analyzed through data reduction, presentation, and conclusion drawing. The research results showed that the BATAS institution has conducted various activities involving students, teachers, and guardians. Not only that, the aspects developed include the nature of faith, the nature of talent and leadership, the nature of learning and reasoning, the nature of individuality and sociality, physical nature, aesthetics, the nature of sexuality and love, the nature of sexuality and love, and the nature of development. The BATAS Institute also conducts activities that support the values of Fitrah education to children, including the nature of faith, the nature of learning and reasoning, the nature of talent and leadership, the nature of individuality and sociality, the nature of sexuality and love, the nature of aesthetics and language, physical nature, and the nature of development.